Gendering Spanish democracy - Threlfall, Mónica (Routledge, 2005)
Addressing aspects of women's experience such as the public spheres of elective politics, public policy-making & the labour market, this book offers an up-to-date critical assessment of gender in Spain.
Keywords: Sex discrimination -- Government policy -- Spain.; Sex role -- Spain.; Discrimination sexuelle -- Politique gouvernementale -- Espagne.; Rôle selon le sexe -- Espagne.; SOCIAL SCIENCE -- Feminism & Feminist Theory.; Sex discrimination -- Government policy; Sex role; Spain